PENGEMBANGAN MULTIMEDIA INTERAKTIF “BATUMBUH” PADA MATERI BAGIAN TUMBUHAN MATA PELAJARAN IPAS UNTUK SISWA KELAS IV SDN BULUSARI 3 - Astin Hadiahti Aulia; Bagus Amirul Mukmin; Farida Nurlaila Zunaidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low learning outcomes, understanding, and learning motivation of grade IV students of SDN Bulusari 3 on plant material due to the use of less varied learning media and teachers still use lecture methods in learning. To overcome this, an interactive multimedia learning media